2021
DOI: 10.1186/s13098-021-00692-x
|View full text |Cite
|
Sign up to set email alerts
|

Circ-ACTR2 aggravates the high glucose-induced cell dysfunction of human renal mesangial cells through mediating the miR-205-5p/HMGA2 axis in diabetic nephropathy

Abstract: Background Circular RNAs (circRNAs) have been considered as pivotal biomarkers in Diabetic nephropathy (DN). CircRNA ARP2 actin-related protein 2 homolog (circ-ACTR2) could promote the HG-induced cell injury in DN. However, how circ-ACTR2 acts in DN is still unclear. This study aimed to explore the molecular mechanism of circ-ACTR2 in DN progression, intending to provide support for the diagnostic and therapeutic potentials of circ-ACTR2 in DN. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…Numerous reports have highlighted circRNAs in the treatment of DN, such as circEIF4G2, hsa_circ_0125310, circTAOK1, and circ-ACTR2 ( Xu et al, 2020 ; Yun et al, 2021 ; Li et al, 2022 ; Zhu et al, 2022 ). A study has indicated that circ-FBXW12 was increased in the serum of DN patients and human MCs by HG-induced.…”
Section: The Role Of Circrnas In Diabetic Complicationsmentioning
confidence: 99%
“…Numerous reports have highlighted circRNAs in the treatment of DN, such as circEIF4G2, hsa_circ_0125310, circTAOK1, and circ-ACTR2 ( Xu et al, 2020 ; Yun et al, 2021 ; Li et al, 2022 ; Zhu et al, 2022 ). A study has indicated that circ-FBXW12 was increased in the serum of DN patients and human MCs by HG-induced.…”
Section: The Role Of Circrnas In Diabetic Complicationsmentioning
confidence: 99%
“…Jie et al found that circ-ACTR2 levels were upregulated in diabetic kidney disease and human renal mesangial cells (HRMCs) treated with high glucose. Silencing circ-ACTR2 expression partially abrogated high-glucose-induced cell proliferation, inflammation, ECM accumulation, and oxidative stress in HRMCs [ 17 ]. In addition, miR-205-5p directly targets the high mobility group AT-hook2 (HMGA2), and HMGA2 downregulation protects against high-glucose-treated HRMCs injury.…”
Section: Discussionmentioning
confidence: 99%
“…circRNA requires specific binding sites for multiple miRNAs to conduct diverse biological roles. Numerous studies reported that circACTR2 could serve as sponge for several miRNAs, such as miR-561 and miR-205-5p [ 21 , 25 ]. Our study firstly demonstrated that miR-221-3p was a direct target of circACTR2.…”
Section: Discussionmentioning
confidence: 99%